Efficiency Dependence of Radiation-Assisted Ceramic Synthesis Based on Metal Oxides and Fluorides on Initial Powder Particle Sizes; Photonics; Vol. 10, iss 10 - Lisitsyn V. M. Viktor Mikhailovich; Polisadova E. F. Elena Fyodorovna; Lisitsyna L. A. Lyudmila Aleksandrovna; Tulegenova A. T. Aida Tulegenkyzy; Denisov I. P. Igor Petrovich; Golkovsky M. G. Mikhail Gedalievich (2023, 2023)
The study is devoted to investigating the efficiency dependence of radiation-assisted ceramic synthesis based on metal oxides and fluorides on initial powder particle sizes. The synthesis was performed for 30 series of ceramic samples, including MgO, Al2O3, ZnO, ZrO2, MgF2, and complex compositions: cerium-activated yttrium-aluminum garnet (Y3Al5O12), spinel AlMgO4, and tungstate MgWO4. The synthesis efficiency was evaluated on the mixture weight magnitude losses, morphology, and relative weight of the obtained ceramic samples. Based on the analysis of the synthesis results and measuring the particle distribution spectra of the initial materials, the criteria for selecting the initial materials were established, and possible explanations for the correlation between synthesis efficiency and the initial materials morphology were proposed.